2011
DOI: 10.1038/mt.2011.48
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Delivery of Tumor Suppressor microRNA Mimics Using a Neutral Lipid Emulsion Inhibits Lung Tumors in Mice

Abstract: MicroRNAs (miRNAs) are emerging as potential cancer therapeutics, but effective delivery mechanisms to tumor sites are a roadblock to utility. Here we show that systemically delivered, synthetic miRNA mimics in complex with a novel neutral lipid emulsion are preferentially targeted to lung tumors and show therapeutic benefit in mouse models of lung cancer. Therapeutic delivery was demonstrated using mimics of the tumor suppressors, microRNA-34a (miR-34a) and let-7, both of which are often down regulated or los… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
439
0
4

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 604 publications
(455 citation statements)
references
References 34 publications
12
439
0
4
Order By: Relevance
“…Thus, it is urgent to find the driving factors during tumorigenesis. miR-34a mimics packaged into a lipid-based delivery of vehicle and given locally or systemically could block tumor growth in mouse models of NSCLC, implying the potential of miRNA replacement therapy in NSCLC (54). Similar results in another study were noted that systemic administration of miR-26 using adeno-associated virus in a mouse model of hepatocellular carcinoma resulted in dramatic suppression of tumor progression without toxicity (52).…”
Section: Future Direction Of Mir-451-based Treatmentsupporting
confidence: 70%
See 1 more Smart Citation
“…Thus, it is urgent to find the driving factors during tumorigenesis. miR-34a mimics packaged into a lipid-based delivery of vehicle and given locally or systemically could block tumor growth in mouse models of NSCLC, implying the potential of miRNA replacement therapy in NSCLC (54). Similar results in another study were noted that systemic administration of miR-26 using adeno-associated virus in a mouse model of hepatocellular carcinoma resulted in dramatic suppression of tumor progression without toxicity (52).…”
Section: Future Direction Of Mir-451-based Treatmentsupporting
confidence: 70%
“…It is well accepted that aberrant miRNA expression is associated with cancer, and miRNAs can influence the sensitivity of tumors to traditional antitumor therapy. Recently, several mouse models provide evidence that miRNAs perform crucial functions in cancer pathogenesis and progression (52)(53)(54). These observations imply that silencing an oncogenic miRNA or restoring a tumor-suppressive miRNA might serve as an effective antitumor therapy.…”
Section: Mir-451 In Cancer Therapymentioning
confidence: 99%
“…Importantly, accumulation of this miRNA in tumour tissues was observed along with low nephro-, cardio-and hepatotoxicity. Similarly, Trang et al [183] reported a significant antineoplastic effect (tumour mass reduction by 60%) by two miRNA mimics, miR-34a and let-7, administered intravenously as a complex with a neutral lipid emulsion, which was preferentially taken up by lung tissue.…”
Section: Preclinical Studiesmentioning
confidence: 91%
“…Unmodified RNA molecules are degraded by RNases and are excreted in the urine [202]. When RNA molecules were administered via the tail vein in mice, they were removed from the bloodstream within less than 30 min [183]. Effective in vivo silencing of specific miRNAs which expression increased pathologically requires the use of anti-miRs characterised by improved biological stability, highly specific miRNA binding and optimal pharmacokinetic properties, which are achieved by chemical modification of the RNA molecule [194].…”
Section: Problems To Overcomementioning
confidence: 99%
“…Secondly, duo to the small particle size, nanoparticles could easily escape from tumor vessels and be kept around tumor tissue for longer time known as enhanced permeability and retention effect (EPR), thus favoring the accumulation and distribution of drugs [13]. More importantly, nanoparticles as a whole were internalized into cells though endocytosis and avoided contact between gene and proteins situated at the surface of cells, leading to the significant improvement on the transfection efficiency of gene [14][15][16].…”
Section: Introductionmentioning
confidence: 99%